Local adaptation to high altitudes functionally modifies the innate immune response in deer mice - Butler, Chloe E., author; Wilsterman, Kathryn, advisor; Angeloni, Lisa, committee member; Titcomb, Georgia, committee member (Colorado State University. Libraries, 2025)
Organisms across the tree of life have repeatedly colonized high altitudes, where they are met by environmental challenges including hypoxia, low temperatures, and increased UV exposure. Over evolutionary timescales, many of these populations of high-altitude residents have adapted to these conditions particularly through changes in metabolically demanding physiological systems ranging from the cardiopulmonary and muscular physiology to reproductive function. Although the immune system is also metabolically demanding to maintain and activate, the immune response is an understudied aspect of animal adaptations to high elevations. In this study, we investigated whether highland-adapted deer mice (Peromyscus maniculatus), a model mammal for high elevation adaptation, display immune-specific adaptations. To study local adaptation in immunity, we employed a conventional immune challenge experiment wherein we injected lowland and highland-derived mice in a common garden environment with a standard dose of the bacterial cell wall component, lipopolysaccharide (LPS), to elicit robust activation of host defense. We collected and analyzed both acute phase responses, including circulating blood glucose, serum corticosterone, and the spleen transcriptomic response to LPS, as well as longer-term responses, such as metabolic recovery and fever, for insight into population-specific strategies. Upon injection of LPS, the metabolic axis of the acute phase response was fundamentally similar between populations. However, highland mice displayed a wider spectrum of body temperatures post-LPS, with an overall more muted fever relative to lowlanders. Behaviorally, we found that lowlanders display a greater degree of sick markers than highlanders do. Using RNAseq, we showed that nearly half of the spleen transcriptome (6202) was LPS-responsive and that many (1052) genes are differentially responsive in a population-specific manner. Importantly, we found nearly 400 genes with additive effects (i.e., population + injection), demonstrating that the transcription response to LPS differs by ancestral origin in a core set of genes. The results of this study unveil key differences in immune regulation strategies affected by the process of high-altitude adaptation.
Keywords: deer mice; lipopolysaccharide (LPS); altitude; Peromyscus maniculatus; evolutionary physiology